Development of a bispecific CDH17-GUCY2C ADC bearing the ferroptosis inducer RSL3 for the treatment of colorectal cancer - Ying Zhang; Jing Du; Xiaohong Cui; Yuhang Ling; Chengwu Tang (Cell Death Discovery)
Abstract Colorectal cancer is a malignant tumor of the colon or rectum, with approximately 150,000 new cases each year. Current treatment strategies, such as surgery, chemotherapy, radiotherapy, and immunotherapy, face challenges ranging from cancer recurrence, drug resistance to significant toxicity. Therefore, these patients urgently need more effective treatments. Ferroptosis, a novel form of cell death characterized by iron-dependent lipid peroxidation, has emerged as a promising new approach for treating colorectal cancer. Inactivation of phospholipid hydroperoxide glutathione peroxidase (GPX4) or the cysteine/glutamate antiporter SLC7A11 leads to the depletion of cellular glutathione (GSH), resulting in lipid peroxidation and subsequent ferroptosis. Here, we found that CDH17 and GUCY2C are co-overexpressed in colorectal cancer cells and developed a bispecific antibody-drug conjugate (BsADC) targeting CDH17 and GUCY2C, conjugated with the ferroptosis inducer RSL3 (a GPX4 inhibitor). Experimental results showed that, compared to monoclonal antibody ADCs, BsADC exhibits better binding and internalization activities, and could inhibit tumor cell proliferation more effectively. Moreover, the BsADC displayed an advantageous safety profile in mice. These findings suggest that the CDH17-GUCY2C BsADC, which induces ferroptosis in tumor cells, could be a promising new treatment for colorectal cancer.